Regulatory challenges: the US experience and its potential relvance - Glazer, Craig; Samudrala, Sridhar; Ravi Sankar, Raman (2000)
This paper addresses two major regulatory challenges: political acceptance of the regulatory process and the regulator's ability to effectively influence and improve the qulatiy of service of the utilities it regulates in the U.S. It also outlines some of the steps that have been taken by regulators related to issues surrounding regulatory independence and customer oriented service quality. - Reproduced.
Keywords: Public utilities - India; Public utilities